Electrochemotherapy Plus IL-2+IL-12 Gene Electrotransfer in Spontaneous Inoperable Stage III–IV Canine Oral Malignant Melanoma - Tellado, Matías Nicolás (2023)
Electrochemotherapy (ECT) is a standard of care in veterinary and human oncology. The treatment induces a well-characterized local immune response which is not able to induce a systemic response. In this retrospective cohort study, we evaluated the addition of gene electrotransfer (GET) of canine IL-2 peritumorally and IL-12 intramuscularly to enhance the immune response. Thirty canine patients with inoperable oral malignant melanoma were included. Ten patients received ECT+GET as the treatment group, while twenty patients received ECT as the control group. Intravenous bleomycin for the ECT was used in both groups. All patients had compromised lymph nodes which were surgically removed. Plasma levels of interleukins, local response rate, overall survival, and progression-free survival were evaluated. The results show that IL-2 and IL-12 expression peaked around days 7–14 after transfection. Both groups showed similar local response rates and overall survival times. However, progression-free survival resulted significantly better in the ECT+GET group, which is a better indicator than overall survival, as it is not influenced by the criterion used for performing euthanasia. We can conclude that the combination of ECT+GET using IL-2 and IL-12 improves treatment outcomes by slowing down tumoral progression in stage III–IV inoperable canine oral malignant melanoma.